The inhibitory effect of natural antioxidants on formation of 2-amino-1-methyl-6-phenylimidazo [4, 5-b] pyridine (PhIP) in a model system - Al-bashabsheh, Zaher Qassim (Kansas State University, 2019)
Heterocyclic amines (HCAs) are a class of mutagenic and carcinogenic compounds generated when muscle foods are cooked at high temperatures. Exposure to HCAs has been linked to human cancers, among them colon, prostate, breast, and pancreatic cancers. Research has focused recently on how HCAs form and how their formation can be inhibited. 2-amino-1-methyl-6-phenylimidazo [4,5-b] pyridine (PhIP) is a common, potentially harmful HCA that forms via the Maillard reaction. The health consequences of consuming HCAs has caused the International Agency for Research on Cancer (IARC) to list PhIP as a “possible human carcinogen.” Antioxidant spices and flavonoid compounds have received considerable attention for their beneficial effect against HCA formation in our daily foods. Consumption of most these antioxidants has been found to protect against various chronic diseases such as cardiovascular diseases and cancers. Chemical model systems help in assessing how HCA formation can be inhibited using different compounds. Chemical model systems are preferred because they limit side reactions that occur in meats, complicating analysis, and thus allow studying the chemical interactions among the precursors of HCAs and applied antioxidants. In this research a model system with 0.011 mmol glucose, 0.022 mmol creatinine, and 0.022 mmol phenylalanine in 90:10 diethylene glycol/water (v/v) was heat-treated at 180°C for 1 hour to test the formation of PhIP. Black and red pepper compounds such as pepper oil, piperine, D-limonene, P-cymene, and capsaicin and flavonoid compounds such as quercetin, apigenin, genistin, phlorizin, and catechin were added individually to the model system at three concentrations (125, 625, and 1250 ppm) to test their effect on PhIP formation. The PhIP contents were assessed using HPLC. The results indicate that four out of five antioxidant components of spices: black pepper oil, piperine, D-limonene, and capsaicin significantly (p < 0.05) reduced PhIP formation, while P-cymene had no significant effect on PhIP formation. All flavonoid compounds also had a significant (p < 0.05) effect on PhIP formation. In addition, binary combinations of two antioxidant spices such as piperine and capsaicin and two flavonoid compounds such as genistin and catechin at 1:0.25, 1:0.5, and 1:1 ratios were also evaluated. Significant (p < 0.05) synergistic effects were observed among all combinations. Our results showed that when antioxidant spices and flavonoid compounds were added to model systems either individually or in combination, they reduced PhIP formation. These findings provide valuable information about antioxidant spices and flavonoid compounds as protective agents against HCA formation.
Keywords: Heterocyclic amine; 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine; Spices; Flavonoid compounds; Model system